Legal Aspects of Medical Action Without Informed Consent in ER Jember Lung Hospital in 2020 - Wahjuni, Edi Wahjuni; Sari, Nuzulia Kumala (Jurnal Dinamika Hukum, 2021)
Before working on a medical action, the doctor must provide information and get approval from a competent patient or next of kin, in the form of informed consent documents. The formulations of these research problems are a) How is the implementation of informed consent for emergency patients at Jember Lung Hospital Emergency Room (ER)? and b) What are the legal aspects of working on a medical action without informed consent in handling the emergency patients? The research  method that  is used  is juridically normative with the method of legal approach. The data sources are from primary and secondary legal sources, and interview results. The research site is at Emergency Room of Jember Lung Hospital. During January to March 2020 there were 956 emergency patients who received medical action at the Emergency Room of Jember Lung Hospital. Four of the 956 emergency patients were taken without informed consent.Keywords: emergency, informed consent and medical treatment